Phase 2 trial of chewing lignocaine soaked gauze: a novel method to reduce gag reflex. - Jasmani, Asraf Haslam (2019)
The gag reflex has been identified as a factor that reduces patient tolerance towards the procedure that involves stimulation of pharyngeal area, hence a better method to reduce the gag reflex is investigated. This study aimed to look at the feasibility of chewing lignocaine soaked gauze to reduce gag reflex besides identifying the optimum dosage of lignocaine. This is phase two, 3 arms, double-blinded, randomized control trial. Participants were divided into three groups, group A received gauze soaked with 160 mg lignocaine, group B received gauze soaked with 320 mg lignocaine and group C received gauze soaked with water. Allocation of participants was determined by computer-generated block randomization. Baseline information, vital signs, gag reflex score and gag reflex location, were recorded. Participants were assessed by two designated individuals at the end of 3 minutes, and gag reflex score is given. Vital signs were monitored and adverse effect recorded. Results were analysed using one-way ANOVA and post hoc test. 30 participants were recruited and divided into three groups with 1:1:1 ratio according to block randomization. Baseline information, vital signs and gag reflex score between groups were compared and were homogenous except age. Gag reflex reduction was seen highest in group B (M = 2.3, SD = 0.67, p = 0.000, t = 10.776, 95% CI = 1.817, 2.813) and no statistically significant changes in the control group (M = 0.1, SD 0.316, p = 0.343, t= 1.000, 95% CI = -0.126, 0.326). There was statistically significant difference in gag reflex severity score between the groups (p = 0.00, F = 27.271). No difference were seen in systolic pressure, diastolic pressure, pulse rate, and oxygen saturation between pretest and posttest for all group. Significant difference in gag reflex score were seen between group A and group C (p = 0.000, 95% CI = -2.90, 1.30) and between group B and group C (p = 0.000, 95% CI = -2.70, -1.10). There was no significant difference between group A and group B (p = 1.00, 95% CI = -1.00, 0.60). Chewing lignocaine soaked gauze is a feasible method to reduce gag reflex and 320 mg lignocaine is not superior to 160 mg of lignocaine in gag reflex reduction.